The structural engineer’s professional training manual - Adams, Dave K. (McGraw-Hill, 2008)
The Structural Engineer's Professional Training Manual offers a solid foundation in the real-world business and problem-solving skills needed in the engineering workplace. Inside This Skills-Building Engineering Resource: • The Dynamics of Training • The World of Professional Engineering • The Business of Structural Engineering • Building Projects • Bridge Projects • Building Your Own Competence • Communicating Your Designs • Engineering Mechanics • Soil Mechanics • Understanding the Behavior of Concrete • Understanding the Behavior of Masonry Construction • Understanding the Behavior of Structural Steel • Understanding the Behavior of Wood Framing.